BOARD MEETING AND SUSTAINABILITY REPORTING OF BANKS IN NIGERIA - Ojuolape Gold, Nusirat; Osayantin Aifuwa, Hope (Copernican Journal of Finance & Accounting, 2022)
A board meeting is an avenue for directors of an organization to carry out their oversight and monitoring functions as well as discuss and meet the request and needs of the stakeholders. Corporate strategies of an organization are taken and implemented when board members meet. Leaning on this fact, this study examined the impact of board meetings on sustainability reporting in listed deposit money banks in Nigeria. A sample of ten (10) listed deposit money banks from 2014 to 2020 was conveniently selected. Descriptive and inferential statistics (panel least squares and logistic regression) was employed to summarize the data and to draw an inference on the population studied. Results from both the panel least squares regression and the binary logit regression revealed that board meetings have no significant impact on sustainability reporting of listed deposit money banks in Nigeria after controlling corporate administration and firm-level attributes. The study concluded that board meetings do not have an impact on sustainability reporting influences sustainability reporting of listed deposit money banks in Nigeria. The study recommends that issues on sustainability should be discussed in the board meeting frequently.